(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
Legal Hermeneutics constitutes an application of Philosophical Hermeneutics,thus rendering it necessary to understand interpretation not only in terms of text,but also fundamentally as an act. Legal Hermeneutics represents an alternative viewof formalism, and for that end, it is crucial that interpretation follows a particularmethod. Legal Hermeneutics requires the thorough study of rhetoric, in terms ofweak rationality from the viewpoint of probability and verisimilitude in view ofdemonstrative science´s strong rationality. The “procedural” nature of Law wherebythe solution to a dispute comes from the final legal solution favours rhetorical persuasion.